Tailoring the Size Distribution of Ultrasound Contrast Agents: Possible Method for Improving Sensitivity in Molecular Imaging - Esra Talu; Kanaka Hettiarachchi; Shukui Zhao; Robert L. Powell; Abraham P. Lee; Marjorie L. Longo; Paul A. Dayton (Molecular Imaging)
Encapsulated microbubble contrast agents incorporating an adhesion ligand in the microbubble shell are used for molecular imaging with ultrasound. Currently available microbubble agents are produced with techniques that result in a large size variance. Detection of these contrast agents depends on properties related to the microbubble diameter such as resonant frequency, and current ultrasound imaging systems have bandwidth limits that reduce their sensitivity to a polydisperse contrast agent population. For ultrasonic molecular imaging, in which only a limited number of targeted contrast agents may be retained at the site of pathology, it is important to optimize the sensitivity of the imaging system to the entire population of contrast agent. This article presents contrast agents with a narrow size distribution that are targeted for molecular imaging applications. The production of a functionalized, lipid-encapsulated, microbubble contrast agent with a monodisperse population is demonstrated, and we evaluate parameters that influence the size distribution and demonstrate initial acoustic testing.